The Life Experience of Sirau Community in Using Post-Flood Bore Wells on Health - Aulia Zulfa; M. Hanif Prasetya Adhi (HealthCare Nursing Journal, 2023)
Drilled well water is one of the main sources for the people of Sirau Village in meeting their daily needs after the flood disaster. During the dry season, residents experience difficulty getting clean water for their daily needs, this is a condition that can be worrying, considering that poor water quality will threaten the health of residents who use it. The purpose of this study is to describe the life experiences of the Sirau Village community in using bore well water after the flood disaster for their health. This research method uses a qualitative descriptive research design with a population of Sirau Village people who have experience using bore well water, this research uses a purposive sampling technique for Sirau Village people who have experience in using bore well water for health for their daily needs and has appropriate criteria with the stipulated, in this case the number of informants involved was 5 people. Data collection techniques through in-depth interviews (in-depth interviews). The data analysis technique taken is the collaizi technique. The results of the study show that there are 3 themes that determine the community's life experiences in using bore well water after the flood disaster. Theme 1 is about drilled well water being the main need during floods, informants said drilled well water is the main source of daily needs during floods. Theme 2 is the lack of drilled wells in the household, the informant said that the community felt a negative impact on their household, such as household appliances becoming crusty, vehicles rusting and clothes turning yellow. Theme 3 is the impact of its use on dental health, the informant said that the teeth become tartar due to the presence of high calcium and when gargling tastes iron. And less good consumed for drinking. The Sirau Village community has life experience in using bore well water after a flood disaster for their health. Communities feel the negative impact on households and health